Dose-dependent rapid-onset akathisia with aripiprazole in patients with schizoaffective disorder - Basu, Ranita (Dove Medical Press, 2006)
A series of cases are reported in which patients on aripiprazole have developed akathisia, although the literature states that the rate is negligible.